More than a feeling: Confidence, uncertainty and macroeconomic fluctuations - Laura Nowzohour; Livio Stracca (European Central Bank (ECB), 2017)
Economists, observers and policy-makers often emphasize the role of sentiment as a potential driver of the business cycle. In this paper we provide three contributions to this debate. First, we critically survey the existing literature on sentiment (considering both confidence and uncertainty) and economic activity. Second, we review existing empirical measures of sentiment, in particular consumer confidence, stock market volatility (SMV) and Economic Policy Uncertainty (EPU), on monthly data for 27 countries, 1985-2016. Third, we identify some new stylized facts based on international evidence. While different measures are surprisingly lowly correlated on average in each country, they are typically highly positively correlated across countries, suggesting the existence of a global factor. Consumer confidence has the closest co-movement with economic and financial variables, and most of the correlations are contemporaneous or forward-looking, consistent with the view that economic sentiment is indeed a driver of activity.
Keywords: E32; E71; F44; G15; G41; 330; animal spirits; confidence; uncertainty; business cycles; dynamic correlations